Cosmetic and Functional Results of External Dacryocystorhinostomy with the Subciliary Incision in a Tertiary Eye Care Hospital, Karachi.: Doi: 10.36351/pjo.v36i2.973 - Qidwai, Nazia; Dawood, Ashraf; Hussain, Munawwar; Inam, Mujahid; Jafri, Adil Salim; Somro, Fayyaz (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess post-operative cosmetic and functional results of external Dacryocystorhinostomy with Subciliary incision in adults with primary naso lacrimal duct obstruction (NLDO). Study Design: Quasi experimental study. Place and Duration of Study: Oculoplasty clinic, Al Ibrahim Eye Hospital, Malir, from July 2016 to September 2017. Material and Methods: Hundred eyes of hundred patients were included. Inclusion criteria was all the patients between the ages of 20 to 70 years having epiphora with diagnosis of NLDO, chronic Dacryocystitis or Mucocele. Patients having ectropion or entropion of inferior punctum were excluded from the study. DCR with intubation was performed through Sub ciliary incision. Inner canthus was photographed with a Nikon D70S digital camera at 1, 3 and 6 months after surgery. Functional success was determined by subjective improvement in watering and patent drainage passage on syringing. Cosmetic result of the scar was assessed by subjective satisfaction of the patient and grading of the subciliary incision scar according to a four level scale by two ophthalmologists. SPSS version 20.0 was used to analyze the data. Result: DCR was done on 100 eyes in 100 patients. Functional and cosmetic success was noted in 90 (90%) eyes. 83 patients attained successful functional outcome, which was confirmed on syringing. On objective grading of the scars by ophthalmologist at the final follow up it was observed that 85 patients had invisible scar. Whereas, 2 had moderately visible scar and 3 patients had minimally visible scar. Subjective grading revealed 85 scars to be invisible, 2 moderately visible and 2 minimally visible. Conclusion: Post-operative cosmetic as well as functional results of subciliary incision in external Dacryocystorhinostomy were found to be highly encouraging.